Die Veränderungen von Klima und Umwelt in der Region Atacama (Nordchile) seit der Letzten Kaltzeit - Messerli, Bruno; Grosjean, Martin; Graf, Kurt; Schottner, Ueli; Schreirer, Hans; Vuille, Mathias (ERDKUNDE, 1992)
The synergistic interaction between subsiding anticyclonic air masses, the drying effect of the cold Humboldt current, and the moisture blocking mountain chain generate extremely dry environmental conditions on the western slope of the Atacama Andes. Even the highest peaks (Volcan Llullaillaco 6739 m) in the continuous permafrost belt above 5600 mare currently free of glaciers. The vegetation between 3100 to 4800 m is too scarce to initiate any soil formation. The precipitation pattern in the Altiplano region can be investigated by monitoring the varying extent of the salar water bodies as seen from satellite data. Terrestrial and limnic ecosystems show major changes since the Last Cold Maximum. Cold and dry conditions are followed by a distinct shift to cool and wet Late Glacial climate (about 400 mm/year) with extended lakes in the Altiplano. Warm and moist environments probably during the Pleistocene/Holocene transition and Early Holocene are indicated by palaeosoils, best developed near 4500 m a.s.l. The warm temperatures lasted during the Holocene, as shown by pollen, whereas present dry conditions were established after approximately 3000 B .P. The palaeoecological findings show that the tropical rainfall belt was reinforced du ring Late Glacial to Early Holocene from the Chungara-Sajama region (18° S) as far south as the Ojos del Salado (27° S). On the contrary, however, the westerlies were relatively stable. It seems that they had no strong influence in the past on the Ojos del Salado (27° S), not even during the Last Cold Maximum. But this clear separation in winter and summer precipitation be comes more and more critical. Too much precipitation is observed in the transition al seasons of spring and autuj11n. Collisions between drops of cold air from the westerlies and warm tropical humid air masses must be analysed more precisely in future research programmes. Human activity, appearing for the first time around 10800 B.P., was always closely related to the environmental conditions, as shown in various archaeological sites. The new findings in the RIO Purifica (5880 B.P.) show that the hypothesis of the silencio arqueo16gico has to be revised. The Atacama region, one of the most arid areas, shows an increasing conflict between a rapidly growing economic activity with expanding urbanization and the sensitive base of natural resources. Also a desert can be exposed to pollution and the groundwater recharge and the water storage capacity are still unknown. The past climatic conditions could be the key to understand the present day limited water resources.